2013
DOI: 10.1186/1559-4106-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Surface anchored metal-organic frameworks as stimulus responsive antifouling coatings

Abstract: Surface-anchored, crystalline and oriented metal organic frameworks (SURMOFs) have huge potential for biological applications due to their well-defined and highly-porous structure. In this work we describe a MOF-based, fully autonomous system, which combines sensing, a specific response, and the release of an antimicrobial agent. The Cu-containing SURMOF, Cu-SURMOF 2, is stable in artificial seawater and shows stimulus-responsive anti-fouling properties against marine bacteria. When Cobetia marina adheres on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 29 publications
(36 reference statements)
1
18
0
2
Order By: Relevance
“…The antibacterial mechanism of this compound is related to the release of Cu and after destroying the wall and membrane and entering the cell, an enzymatic activity is targeted in the bacterium, which ultimately leads to a reduction in gene expression (26,27 (28,29). Similar to previous studies (30)(31)(32)(33), the present study found that the antibacterial activity of nanostructures includes metal/metal oxide copper. The real-time PCR method is sensitive and commonly used to detect gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…The antibacterial mechanism of this compound is related to the release of Cu and after destroying the wall and membrane and entering the cell, an enzymatic activity is targeted in the bacterium, which ultimately leads to a reduction in gene expression (26,27 (28,29). Similar to previous studies (30)(31)(32)(33), the present study found that the antibacterial activity of nanostructures includes metal/metal oxide copper. The real-time PCR method is sensitive and commonly used to detect gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…New MOFs based on different metals such as Co, Zn or Cu have also emerged. In most cases, these MOFs have been successfully tested towards heterotrophic organisms like Pseudomonas putida, E. coli, Saccharomyces cerevisiae or S. aureus (Aguado et al, 2014;Wang et al, 2015;Wojciechowska et al, 2012;Zhuang et al, 2012) and to marine bacteria as Cobetia marina (Sancet et al, 2013). However, studies to examine the biocidal effect of MOFs to photosynthetic organisms as cyanobacteria or algae are lacking (Wyszogrodzka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that SURMOFs can act as a release matrix for pharmaceuticals and other drugs. This study opens up the possibility of applying SURMOFs in the biochemical field [391,392].…”
Section: Mof Thin Filmsmentioning
confidence: 91%